Preoperative systemic inflammatory response index predicts the prognosis of patients with hepatocellular carcinoma after liver transplantation - Cui, Songping; Cao, Shuang; Chen, Qing; He, Qiang; Lang, Ren (Frontiers in Immunology, 2023)
Background: There is growing evidence that preoperative inflammatory status is a predictor of malignancy prognosis. The aim of this study was to investigate the value of preoperative inflammatory biomarkers in predicting long-term outcome of liver transplantation (LT) for hepatocellular carcinoma (HCC). Method: We retrospectively collected patients who received LT for HCC in our hospital between January 2010 and June 2020. Demographic, clinical data, laboratory data and outcome variables were obtained. The predictive value of inflammatory biomarkers was evaluated by the area under the curve (AUC) of the receiver operating characteristic curve. Univariate and multivariate Cox proportional hazard analyses were used to determine the effectiveness of inflammatory biomarkers in predicting outcomes. Results: The study included 218 patients with a mean age of 53.9±8.5 years. The AUC of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune inflammation index (SII), and systemic inflammatory response index (SIRI) for overall survival (OS) were 0.741, 0.731, 0.756, 0.746 and 0.749, respectively. Cox proportional hazards model indicated that SIRI>1.25 was an independent poor prognostic factor for OS (hazard ratio [HR]=2.258, P=0.024). PLR>82.15 and SIRI>0.95 were independent poor prognostic factors for disease-free survival (HR=1.492, P=0.015; HR=1.732, P=0.008, respectively). Survival analysis showed that patients with high preoperative SIRI, PLR had a significantly worse prognosis (P<0.001). Conclusion: Our findings suggested that SIRI and PLR were useful prognostic markers for predicting HCC patients after LT.